Diplomatic or eclectic critical editions of the Hebrew Bible? Considering a third alternative - Prinsloo, Gert T. M. (HTS teologiese studies, 2022)
Ever since the publication of the third edition of Rudolph Kittel’s Biblia Hebraica (BHK3) to the present gradual production of the Biblia Hebraica Quinta (BHQ) so-called editiones criticae minores of the Hebrew Bible are diplomatic editions. The Codex Leningradensis, dating from 1008/9 CE, is used as the base text, and the Biblia Hebraica text editors note significant variants in other Hebrew manuscripts and/or the ancient versions in eclectic fashion in a text-critical apparatus. The Hebrew University Bible Project (HUPB) also publishes a diplomatic text based on the Codex Aleppo but with a more detailed text-critical apparatus. The Hebrew Bible: A Critical Edition (HBCE) follows a different route, traditionally more familiar in the production of critical editions of the Septuagint and New Testament, namely to publish an eclectic edition. The text editors produce a theoretical, reconstructed text of what they regard as the ‘correct’ reading after careful consideration and weighing of variants in all available textual witnesses. I argue that critical editions of the Hebrew at the disposal of Hebrew Bible scholars, whether based on a diplomatic or eclectic text, have two inherent weaknesses, namely eclecticism and lack of context. Taken together, these shortcomings might be classified as subjectivism. I propose at least considering the alternative of a synoptic text-critical approach beyond the diplomatic-eclectic dichotomy.Contribution: This research critically reviews the current diplomatic/eclectic approaches in the production of scholarly Hebrew Bibles and proposes at least considering a third alternative, namely a synoptic approach